Integration of Science from the Perspective of the Qur'an - Huzaimah; Kusnadi; Aristophan Firdaus (Penerbit Hellow Pustaka, 2026)
The integration of general knowledge and religion in modern Islamic education is a crucial issue in the era of globalization and technological advancement. The main problem raised is the dichotomy between religious knowledge and general knowledge, which hinders the development of holistic Islamic education. The aim of this research is to explore the challenges and opportunities in the integration process, with a focus on philosophical, theological and practical approaches. The research method used is a literature review with qualitative analysis of relevant literature. The research results show that the integration of general knowledge and religion can increase the relevance of Islamic education to the needs of our time, although structural and paradigmatic challenges still constitute the main obstacles. Support from various parties is the key to successfully implementing this integration.